2017
DOI: 10.1021/acscatal.6b03646
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of the Influence of Pore Geometry on Monomolecular Cracking and Dehydrogenation of n-Butane in Brønsted Acidic Zeolites

Abstract: Recent experimental work has shown that variations in the confinement of n-butane at Brønsted acid sites due to changes in zeolite framework structure strongly affect the apparent and intrinsic enthalpy and entropy of activation for cracking and dehydrogenation. Quantum chemical calculations have provided good estimates of the intrinsic enthalpies and entropies of activation extracted from experimental rate data for MFI, but extending these calculations to less confining zeolites has proven challenging, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 77 publications
5
73
0
Order By: Relevance
“…Until recently,t hese adsorption parameters were either estimated by extrapolationo fl ow-temperature measurements, [4,14,17,18] or by molecular simulations. [4,12,16,28] However,s tate of the art simu-lations predict as trong influence of temperature on the adsorptione ntropy, D ads S, [7,20,25,[29][30][31] which was assumed to be negligible in previous studies. On this ground, the variations in apparent rate coefficientsw ere initially accounted by changes in adsorption parameters, K8 ads , [9-11, 14, 15, 27] and more recently by changes in the pre-exponential factor of the intrinsic rate constant, and hence, activation entropy DS°.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently,t hese adsorption parameters were either estimated by extrapolationo fl ow-temperature measurements, [4,14,17,18] or by molecular simulations. [4,12,16,28] However,s tate of the art simu-lations predict as trong influence of temperature on the adsorptione ntropy, D ads S, [7,20,25,[29][30][31] which was assumed to be negligible in previous studies. On this ground, the variations in apparent rate coefficientsw ere initially accounted by changes in adsorption parameters, K8 ads , [9-11, 14, 15, 27] and more recently by changes in the pre-exponential factor of the intrinsic rate constant, and hence, activation entropy DS°.…”
mentioning
confidence: 99%
“…On this ground, the variations in apparent rate coefficientsw ere initially accounted by changes in adsorption parameters, K8 ads , [9-11, 14, 15, 27] and more recently by changes in the pre-exponential factor of the intrinsic rate constant, and hence, activation entropy DS°. [7,25,31,32] Ak ey to resolve these discrepancies is the simultaneous determination of active site coverage and apparent rates at reactionc onditions. This temperature dependence has al arge influence on the estimates of alkane coverage and hence the estimates of intrinsic rates.…”
mentioning
confidence: 99%
“…This work represents a major advance toward the understanding of the effects of zeolite structure on the intrinsic kinetics of monomolecular cracking. However, we believe that a few points made by the authors in reference to our work, which deals with the effects of zeolite structure on intrinsic kinetics for n ‐butane and n ‐hexane cracking and dehydrogenation using a combination of experimental measurements and configurational‐bias Monte Carlo (CBMC) simulations, need additional clarification. We would also like to highlight some key consistencies between our reported results and those of Kadam et al …”
Section: Values Of the Intrinsic Activation Energy And Entropy For Thmentioning
confidence: 98%
“…Until recently, this has not been attempted using experimental adsorption measurements because of the tendency of the alkane to relocate to siliceous parts of the framework at high temperature, and because of the occurrence of chemical reactions at temperatures above ≈600 K . Moreover, several theoretical studies have shown that the distribution of adsorbed alkanes within the pores of a zeolite changes with the adsorption temperature, and consequently any insights gleaned from low temperature adsorption experiments are unlikely to be transferrable to reaction temperatures . To overcome these concerns, Janda et al.…”
Section: Experimental Studies Of Reaction At Brønsted Acid Sitesmentioning
confidence: 99%
“…(4) and (5)] to determine the intrinsic activation parameters for the overall consumption of each alkane, normalized by the number of C−C bonds . The advantage of the CBMC simulations is that they properly account for the changes in the distribution of alkane amongst different environments in the zeolite at high temperature and they also account for the greater number of configurations explored by the alkane in the vicinity of the active site at high temperatures …”
Section: Experimental Studies Of Reaction At Brønsted Acid Sitesmentioning
confidence: 99%